Stock Depreciation and Company Valuation of PT Express Transindo Utama, Tbk - Fiqri Darmawan, Ichsan; Budi Nugroho, Anggoro (The Indonesian Journal of Business Administration, 2016)
Abstract. PT Express Transindo Utama (Express Group) is the second largest taxi company in Indonesia. Currently Blue Bird is still market leader but Express is showing signs of aggressive expansion. On 2 November 2012 Express debuted on the Indonesia Stock Exchange (making it Indonesia's first publicly traded cab service) by selling 49 percent of its equity, raising IDR 588.7 billion (about USD $60 million). However, PT Express Transindo which listed as PT Express Transindo Utama, Tbk (TAXI) stocks depreciates from Rp.1.200 in 2 January 2015 to Rp. 105 per share in 30 December 2015. In order to find the cause of the phenomena, event study used to determine the stock’s price change. Independent sample test and Mann Whitney U test conducted for the two events which estimated as the cause of PT Express Transindo Utama Tbk stocks depreciation during 2015. Those two events which eastimated to be relate with the bearish price of the TAXI stock is the Gojek Launching in 10 February 2015 and Saratoga Cancellation Acquisition in 7th October 2015. This final project also measured the intrinsic value of PT Express Transindo Utama Tbk, by using Discounted Cash Flow method valuation. The intrinsic value of PT Express Transindo Utama Tbk is currently undervalued at Rp 1201,14 per share compare with the market price at Rp 105 at the end of 2015. However, the company suffered the negative cash in the end od projected years due to the obligations to pay Rp 1 trillion company bonds. In order to improve their financial performance this study propose the business solution, which are, optimizing the Working day in Express Brand’s fleet, Increasing the Express fleet daily payment Improving the Eagle Brand fleets occupancy Increasing the revenue from Value Added Transportation Business and also developing their own mobile based application. Keyword:  Taxi, Event Study, Discounted Cash Flow, Relative Valuation, Financial Analysis